UPAYA PENCEGAHAN BULLYING MELALUI PEMBELAJARAN SOSIAL EMOSIONAL PADA PESERTA DIDIK DI SMA NEGERI 1 KALAPANUNGGAL - Arrobi, Jimatul; Siti Sarah; Iaskah Nur Amilah; Yogi; Zenitha Astrid Tanring (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the prevalence of bullying in school environments, which continues to occur and has negative impacts on students’ development, including academic, social, and emotional aspects. Bullying behavior not only harms victims but also affects perpetrators and the overall learning climate. Therefore, systematic efforts are needed to understand the forms of bullying and effective strategies to address it. This study aims to describe the forms of bullying and analyze the impact of implementing a social-emotional learning approach on students’ behavior. This research employs a qualitative method with a case study approach conducted at SMA Negeri 1 Kalapanunggal. The data sources were obtained from students, and data were collected through observation and document analysis. The data analysis techniques included data reduction, data display, and conclusion drawing. The results show that bullying in the school takes the form of verbal, physical, and social bullying. To address this issue, a social-emotional learning approach is integrated through an anti-bullying program based on five CASEL competencies: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. The implementation of this approach has been shown to help students manage their emotions, enhance empathy, and build more positive social relationships, thereby reducing bullying behavior in the school environment.